Ferroelectric transistors with asymmetric double gate for memory window exceeding 12 V and disturb-free read. Issue 38 (22nd September 2021) - Mulaosmanovic, Halid; Kleimaier, Dominik; Dünkel, Stefan; Beyer, Sven; Mikolajick, Thomas; Slesazeck, Stefan
Abstract : The asymmetric double-gate hafnium oxide based ferroelectric field-effect transistor displays a memory window exceeding 12 V and multi-level storage of 4 bit per cell with a disturb-free read. Abstract : Ferroelectric field-effect transistors (FeFETs) with a single gate structure and using the newly discovered ferroelectric hafnium oxide as an active material are attracting considerable interest for nonvolatile memory devices. However, such FeFETs struggle to achieve a large separation between the two logic states (memory window, MW) because of the thickness limitations of the ferroelectric film. Moreover, they are affected by detrimental disturbs coming from the read operation because of the shared write and read paths. Therefore, significant performance improvements are needed for the device to compete with established memory technologies like flash. Here, we present an asymmetric double-gate FeFET structure, where only one gate stack comprises the ferroelectric layer. We propose a novel read operation at the non-ferroelectric gate and demonstrate an amplified MW exceeding 12 V thanks to the enhanced body effect factor and the increased sensitivity of the transfer characteristics to the ferroelectric polarization. As a result, the above physical limitation is circumvented, thus by far outperforming the MW values reported in the literature. Based on this, we implement the multi-level cell storage featuring 4 bits per cell and stable data retention. Finally, an essential benefit originating from the separated write and read paths in our structure is exploited to demonstrate the fully disturb-free read operation. Besides memory, this could be particularly favorable for those neuromorphic and in-memory computing concepts with an occasional update of the stored variable but a very frequent read.